Efeitos cardiovasculares do tratamento crônico com testosterona em ratos wistar - Rouver, Wender do Nascimento (2015)
Cardiovascular diseases are the leading cause of death in world and the fact that men are more affected meant that the testosterone was thought of as a harmful substance to the cardiovascular system. However, more recent studies have challenged this hypothesis and suggest a beneficial role of this hormone on the cardiovascular system. Nevertheless, the effects of chronic testosterone treatment on vascular endothelium-dependent function, have not been fully clarified. Thus, the present study was designed to determine the effects of chronic treatment with different doses of testosterone on coronary vascular reactivity induced by bradykinin. Males Wistar rats were used with 10 weeks of age, who were separated in Sham and castrated groups. Castrated rats were immediately treated with physiological (Physio, 0.5 mg / kg / day, sc) and supraphysiological (Supra, 2.5 mg / kg / day, sc) doses of testosterone for 15 days. Systolic blood pressure (SBP) was measured by tail plethysmography at the end of treatment. After euthanasia, the hearts were removed and coronary vascular reactivity was assessed by retrograde perfusion technique Langendorff. Dose response curve of bradykinin (BK) was then constructed by inhibition with 100 mM L-NAME, 2.8 uM indomethacin (INDO), L-NAME + INDO or L-NAME + INDO + 0.75 uM clotrimazole (CLOT). Data were expressed as mean ± SEM and the comparison between groups was performed by one or two-way ANOVA followed by the post-hoc Tukey test (p <0.05). We observed significant coronary endothelium-dependent vasodilation induced by BK, which was abolished in castrated group and restored in Physio and Supra group. After conjugated inhibition of endothelium-dependent relaxation factors (NO, PGI2 and EDHF), we found that vasodilation was abolished in all groups. Castration modulated lipid and hormonal profile, as well as reduced body weight and replacement with testosterone was able to restore all of these parameters. We also observed a significant increase in blood pressure in Supra group. Our data lead us to conclude that testosterone physiological concentrations may play a beneficial role in cardiovascular system to maintain a favorable environment for the action of an endothelium-dependent vasodilator, with no increase in SBP, which makes this steroid a possible tool in hormone therapies.